2022
DOI: 10.1109/te.2022.3144943
|View full text |Cite
|
Sign up to set email alerts
|

Building a Quantum Engineering Undergraduate Program

Abstract: A roadmap is provided for building a quantum engineering education program to satisfy U.S. national and international workforce needs.Background: The rapidly growing quantum information science and engineering (QISE) industry will require both quantumaware and quantum-proficient engineers at the bachelor's level.Research Question: What is the best way to provide a flexible framework that can be tailored for the full academic ecosystem?Methodology: A workshop of 480 QISE researchers from across academia, govern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 97 publications
0
39
0
Order By: Relevance
“…It is argued that education has to link more business schools to the quantum industry [67], and that there is a need to raise the "profile of quantum technologies amongst the public and within education syllabuses to facilitate discussions about the role of these technologies in society" [65] (p. 4). It is noted that "along with issues of diversity, equity, and inclusion, consideration of social, societal, ethical and sustainability issues of QISE would be beneficial, in line with directions in engineering education worldwide" [83] (p. 10). It is recognized that there is a need for increased "social support for undergraduate researchers through designated cohorts" because this "can help them build community with their peers and see themselves as engineers and scientists, something that is often difficult for marginalized students who do not see themselves reflected in the celebrated leaders of the field" [83] (p. 16).…”
Section: Education and Quantum Technologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is argued that education has to link more business schools to the quantum industry [67], and that there is a need to raise the "profile of quantum technologies amongst the public and within education syllabuses to facilitate discussions about the role of these technologies in society" [65] (p. 4). It is noted that "along with issues of diversity, equity, and inclusion, consideration of social, societal, ethical and sustainability issues of QISE would be beneficial, in line with directions in engineering education worldwide" [83] (p. 10). It is recognized that there is a need for increased "social support for undergraduate researchers through designated cohorts" because this "can help them build community with their peers and see themselves as engineers and scientists, something that is often difficult for marginalized students who do not see themselves reflected in the celebrated leaders of the field" [83] (p. 16).…”
Section: Education and Quantum Technologiesmentioning
confidence: 99%
“…It is noted that "along with issues of diversity, equity, and inclusion, consideration of social, societal, ethical and sustainability issues of QISE would be beneficial, in line with directions in engineering education worldwide" [83] (p. 10). It is recognized that there is a need for increased "social support for undergraduate researchers through designated cohorts" because this "can help them build community with their peers and see themselves as engineers and scientists, something that is often difficult for marginalized students who do not see themselves reflected in the celebrated leaders of the field" [83] (p. 16). It is suggested that "a quantum awareness or concepts course" on the undergraduate level, if possible in the first year, "to introduce students to the field early" would be beneficial [83] (p. 18), and that new courses are already being developed [84].…”
Section: Education and Quantum Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in engineering and CS education have engaged in similar efforts in more interdisciplinary QIS contexts [26,27]. Recent work has begun to create a roadmap for comprehensive QIS education at the undergraduate level and beyond [28,29].…”
Section: B Prior Workmentioning
confidence: 99%